Exploring the impact of gender-related variables on health measures and perceived stress - Picó-Pérez, Maria; Coelho, Marisa S.; Vieira, Rita; Machado-Sousa, Mafalda; Morgado, Pedro (Frontiers in Psychology, 2025)
IntroductionDespite its relevance for health outcomes, only recently gender has begun to be explored in the scientific literature, typically using a rigid binary framework. To tackle this, the Stanford Gender-related Variables for Health Research (GVHR) was developed to analyze gender from a multidimensional perspective. We aim to use our Portuguese version of the GVHR and analyze its association with health outcomes, including perceived stress.MethodsTo this aim, 351 participants completed the GVHR scale, sociodemographic, and health information (including the Perceived Stress Scale, PSS-10). A Confirmatory Factor Analyses (CFA) was first performed, and logistic and linear regressions were used to explore the association between gender and health-related variables.ResultsAll measures of CFA showed appropriate goodness of fit. Regarding regression models, gender discrimination and higher levels of risk-taking were associated with binge drinking. Lower social support and risk-taking, and being male, were associated with being overweight. Regarding stress, it was positively associated with discrimination and work strain, while it was negatively associated with social support, emotional intelligence and risk-taking. Finally, discrimination and work strain were positively associated with mental health worsening and activity limitations, while social support was negatively associated with mental health worsening.DiscussionIn conclusion, by approaching gender from a multidimensional perspective we detected specific factors influencing health outcomes, showing that the relational aspects of gender are particularly relevant for mental health.